Intraductal Papillary-Mucinous Neoplasm of the Pancreas Penetrating to the Stomach and the Common Bile Duct - Goto, Norihiro; Yoshioka, Masahiro; Hayashi, Motohito; Itani, Toshinao; Mimura, Jun; Hashimoto, Kimio (JOP. Journal of the Pancreas, 2012)
<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "MS Mincho"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;" lang="EN-US">Context <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "MS Mincho"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;" lang="EN-US">Intraductal papillary mucinous neoplasm (IPMN) of the pancreas occasionally penetrates to others organs. We present a case of IPMN penetrating to the stomach and the common bile duct. Case report A 75-year-old man was admitted to the hospital because of epigastric pain. Computed tomography (CT) showed a papillary tumor protruding into the markedly dilated main pancreatic duct and splenic vein obstruction. The tumor was diagnosed as IPMN arising in the main duct, but he rejected surgery and he was followed without treatment. One year later, gastroduodenoscopy revealed gastropancreatic fistula and we were able to pass an endoscope through the fistula and directly examine the lumen of the main pancreatic duct and the papillary tumor adjacent to the fistula. Absence of malignant cells on histopathology suggested mechanical penetration rather than invasive penetration. CT showed splenic vein reperfusion due to decreased inner pressure of the main pancreatic duct. Two and a half years later, CT revealed biliopancreatic fistula formation. Endoscope biliary drainage was performed but failed. Despite jaundice, he is still ambulatory and seen in the clinic three years after the first admission. Conclusions We have experienced a case of IPMN penetrating to the stomach and the common bile duct that has taken a slow course. It represents the importance of distinguishing mechanical penetration from invasive penetration as well as mechanical splenic vein obstruction from splenic vein invasion.